(untitled) (Research, Society and Development, 2020)
Thermal lesions constitute a differentiated type of skin wound, requiring adequate attention. Thus, the objective of this study was to evaluate the therapeutic action of Bixa orellana L. and Triticum aestivum extracts as active in topical formulations against 2nd degree thermal lesions in an experimental model. First, the annatto oil compounds were identified. In the trial, experimentally induced wounds were treated daily with: formula containing annatto oil and aqueous wheat extract (LCFT 2001), formula containing annatto oil and ethanolic wheat extract (LCFT 2002), commercial ointment (CP), no treatment (CN). At two, five, eight, 14 and 25 days, the presence of exudate, edema, necrosis, crust, granulation and epithelialization was clinically evaluated. Also, the lesion area was determined, and skin samples were collected for histological and tensiometric evaluation. Clinically, at eight days, the formulas presented lower percentage of crust than the control groups and LCFT 2001 showed higher percentage of granulation. Histologically, at five days, LCFT 2002 presented angiogenesis similar to CP, but less inflammation. At eight days, the formulas contained angiogenesis in arches, whereas the control groups fine angiogenesis and the LCFT 2001 showed exuberant inflammation, while the CP with moderate inflammation. It is concluded that formulations containing extracts of wheat and annatto stimulate the healing of thermal lesions.